The Flouting Maxims in Indonesia Lawyers Clubs (ILC) Talk Show Program on TV One (KPK VS POLRI: Ujungnya sampai di mana?) - Umroh Umroh; Eddy Setia (Universitas Negeri Medan, 2016)
The objectives of study are to find out the maxims which are flouted, to find out the process of dominant flouting maxims and to find out the reasons of dominant flouting maxims. This research is conducted by document qualitative analysis research design. The data are the utterances of some conversations which were flouted. The data source of this research was taken from ILC Talk Show with the topic “KPK VS POLRI: Ujungnya sampai dimana?” broadcast on February 15th, 2014 that was obtained from the video on internet. The data were analyzed by using Miles and Huberman (1994). The result shows that all types of maxims are flouted by participants namely: maxim of quantity, maxim of quality, maxim of relevance and maxim of manner.. The second most frequently is flouting maxim of relevance twenty-one occurrences, flouting maxim of manner with six occurrencesand flouting maxim of quality with three occurrences. The most dominant reasons were usually carried out by giving detail explanation to give more information to stress and to expect something in order to make the intended meaning clearer for the listener to follow. It is suggested the reader comprehend the flouting maxim deeply so that they can choose which one is appropriate and which one is not applied in their conversation. Key words: flouting maxim, Indonesia lawyers club, talk show